DOMINANT FACTORS CHANGE OF LAND FUNCTION IN RAPUAN ROAD CORRIDOR UBUD BALI DUE TO TOURISM ACTIVITIES - Putri, Ni Nyoman Samitri; Dwijendra, Ngakan Ketut Acwin (ASTONJADRO, 2022)
Bali is the most popular tourist destination with Ubud one of the tourist destinations with its beautiful landscapes and rice fields. Mas Village, Ubud is one of the tourist villages that has been inaugurated by the Gianyar Regency Government based on the Decree of the Gianyar Regent Number 429/E-02/HK/2017 regarding the establishment of a Tourism Village. Jalan Rapuan which is located in Tarukan Tourism Village, Mas is one of the strategic corridors in Mas Tourism Village because it is a stretch of rice fields that has a high tourism selling value. The purpose of this study is to identify changes in land use in 2013-2021 due to tourism activities seen from the aspects that have a dominant influence on land use changes. Quantitative method is the method used with primary and secondary data collection methods and stages of analysis in the form of descriptive analysis of tourism activities in Mas Village, statistical-descriptive analysis of land use change with overlay analysis on the Jalan Rapuan corridor. The results showed that there was a change in land use along the Rapuan corridor in 2013-2021 by 14% of the non-built land to be built in the form of tourist accommodation and housing. The indicators analyzed by factor analysis were able to explain important factors, namely external factors of 31.69%, internal factors of 23.821% and regulatory factors of 17.218% with a total of factors able to explain land use change of 72.73%.